Identification of a distinct lipidomic profile in the osteoarthritic synovial membrane by mass spectrometry imaging. Issue 5 (May 2021) - Rocha, B.; Cillero-Pastor, B.; Ruiz-Romero, C.; Paine, M.R.L.; Cañete, J.D.; Heeren, R.M.A.; Blanco, F.J.
Summary: Objective: Synovial inflammation is one of the most characteristic events in different types of arthritis, including Osteoarthritis (OA). Emerging evidence also suggests the involvement of lipids in the regulation of inflammatory processes. The aim of this study was to elucidate the heterogeneity and spatial distribution of lipids in the OA synovial membrane and explore their putative involvement in inflammation. Method: The abundance and distribution of lipids were examined in human synovial membranes. To this end, histological cuts from this tissue were analysed by matrix-assisted laser desorption ionization - mass spectrometry imaging (MALDI-MSI). The lipidomic profile of OA synovium was characterized and compared with healthy and other forms of inflammatory arthropathies as Rheumatoid Arthritis (RA) and Psoriatic Arthritis (PsA) using principal component analysis and discriminant analysis methods. Lipid identification was undertaken by tandem MS analyses and database queries. Results: Our results reveal differential and characteristic lipidomic profiles between OA and control samples. Specifically, we unveiled that OA synovium presents elevated levels of phosphatidylcholines, fatty acids and lysophosphatidic acids and lower levels of lysophosphatidylcholines compared to control tissues. The spatial distribution of particular glycerophospholipids was also correlated with hypertrophic, inflamed or vascularized synovial areas. Compared with other inflammatory arthritis, the OA tissue showed lower amounts of phosphatidylethanolamine-based plasmalogens. Conclusions: This study provides a novel insight into the lipid profiles of synovial membrane and differences in abundance between OA and control tissues. The lipidomic alterations improves understanding of the pathogenic mechanisms of OA and may be important for its diagnosis.